Flavoprotein fluorescence elevation is a marker of mitochondrial oxidative stress in patients with retinal disease - Ahsanuddin, Sofia; Rios, Hernan A.; Otero-Marquez, Oscar; Macanian, Jason; Zhou, Davis; Rich, Collin; Rosen, Richard B. (Frontiers in Ophthalmology, 2023)
Purpose: Recent studies of glaucoma and diabetic retinopathy have demonstrated that flavoprotein fluorescence (FPF) can be utilized as an indicator of retinal mitochondrial oxidative stress. However, comprehensive assessment of the validity and reliability of FPF in differentiating between healthy and diseased eyes across multiple disease states is lacking. Here, we determine the specificity and sensitivity of FPF in discriminating between healthy and diseased eyes in four leading causes of visual impairment worldwide. We also evaluate the association between FPF and visual acuity. Methods: 88 eyes were included in the present cross-sectional observational study. Eyes were imaged non-invasively using the OcuMet Beacon (OcuSciences, Ann Arbor, MI). The macula was illuminated using a narrow bandwidth blue light (455 – 470 nm) and fluorescence was recorded using a narrow notch filter to match the peak emission of flavoproteins from 520 to 540 nm. Nonparametric Kruskal-Wallis Tests with post-hoc Mann Whitney U tests with the Holm-Bonferroni correction were performed to assess differences in FPF intensity, FPF heterogeneity, and best corrected visual acuity (BCVA) between the five groups. AUROC analysis was used to determine the sensitivity of FPF in discriminating between diseased and healthy eyes. Spearman rank correlation coefficients were calculated to assess the relationship between FPF and BCVA. Results: AUROC analysis indicated that FPF intensity is highly sensitive for detecting disease, particularly for exudative AMD (0.989; 95% CI = 0.963 – 1.000, p=3.0 x 107). A significant difference was detected between the FPF intensity, FPF heterogeneity, and BCVA across all five groups (Kruskal-Wallis Tests, p = 1.06 x 10-8, p = 0.002, p = 5.54 x 10-8, respectively). Compared to healthy controls, FPF intensity values were significantly higher in RVO, DR, exudative AMD, and CSR (p < 0.001, p < 0.001, p < 0.001, and p = 0.001, respectively). Spearman rank correlation coefficient between FPF intensity and BCVA was ρ = 0.595 (p = 9.62 x 10-10). Conclusions: FPF is highly sensitive for detecting the presence of retinal disease. These findings are consistent with the hypothesis that there is elevated oxidative stress in all of these conditions. FPF intensity is moderately correlated with BCVA.